In vitro effects of both dopaminergic and enkephalinergic antagonists on the ovarian growth of Cherax quadricarinatus (Decapoda, Parastacidae), at different periods of the reproductive cycle - Cahansky, Alejandra Valeria (2011)
The in vitro effect of both spiperone (dopaminergic antagonist) and naloxone (enkephalinergic antagonist), was assayed on small pieces of ovary dissected from C. quadricarinatus females, with the eventual addition of some neuroendocrine organs, such as thoracic ganglion or eyestalk tissue. The incorporation of tritiated leucine by the ovary was measured in order to estimate the ovarian growth. During the post-reproductive period, both mentioned antagonists were able to significantly stimulate the ovary in the presence of thoracic ganglion, but did not produce any significant effect in the preparation containing ovary and eyestalk tissue, or only ovary. No significant effects of the assayed antagonists were noted during the pre-reproductive period. These results were in accordance with previous models describing the neuroendocrine control of crustacean reproduction, and represent new findings about the hormonal context in different periods of the reproductive cycle of crayfish. Besides, by means of the experimental combination of the tested antagonists with dopamine or met-enkephalin, a new model dealing with the interaction of these two neurotransmitters on the hormonal secretion of thoracic ganglion has been proposed.